2018
DOI: 10.5391/ijfis.2018.18.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Deep Learning Algorithms for MNIST in Real-Time Environment

Abstract: Recognizing handwritten digits was challenging task in a couple of years ago. Thanks to machine learning algorithms, today, the issue has solved but those algorithms require much time to train and to recognize digits. Thus, using one of those algorithms to an application that works in real-time, is complex. Notwithstanding use of a trained model, if the model uses deep neural networks it requires much more time to make a prediction and becomes more complicated as well as memory usage also increases. It leads r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Moreover, the CapsNet uses the dynamic routing algorithm to achieve data transmission between the capsule layers (as shown in Fig. 10), which overcomes the shortcomings of the traditional pooling layer 34 . In the dynamic routing algorithm, a non-linear "squashing" function (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the CapsNet uses the dynamic routing algorithm to achieve data transmission between the capsule layers (as shown in Fig. 10), which overcomes the shortcomings of the traditional pooling layer 34 . In the dynamic routing algorithm, a non-linear "squashing" function (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [21] examined the performance of logistic regression models in real-time to demonstrate their effectiveness. Regarding IoT networks, ref.…”
Section: Related Workmentioning
confidence: 99%
“…Meier et al [31], used an ensemble of 25 neural networks and Ciresan et al [11] used a 6-layers neural network. Palvanov et al [37] showed how Deep Residual Networks recognises digits much faster than the traditional CNN due to its inherent architecture consisting of shortcut connections.…”
Section: Handwritten Digit Recognitionmentioning
confidence: 99%